Pengaruh Board Diversity terhadap Stabilitas Bank: Bukti dari Bank Tercatat di Indonesia - Pananda Pasaribu; Masripah Masripah (Jurnal Pasar Modal dan Bisnis, 2022)
This research tries to examine the effect of board diversity, namely gender, education, and age on bank stability (credit risk and risk-taking decisions). This study uses listed banks in Indonesia during the period 2010 and 2020, which include foreign banks and governments banks. The estimation method used is panel data regression with fixed-effect method to anticipate endogeneity problems that may arise when analyzing the diversity of directors/commissioners on bank stability. The results of the descriptive analysis show that there is a tendency for Indonesian banks to choose individuals who fill the boards with homogeneous characteristics, particularly the low partipicipation of females on board. However, there is a positive trend during the observation period to increase the diversity of characteristics in these important positions. The results of the regression analysis show that various board diversity can affect bank stability, but the relationship may be affected by bank size, in which large banks may obtain most of benefits of board diversity.